Complicated Grief: What to Expect After the Coronavirus Pandemic - Gesi, Camilla; Carmassi, Claudia; Cerveri, Giancarlo; Carpita, Barbara; Cremone, Ivan Mirko; Dell'Osso, Liliana (Frontiers in Psychiatry, 2020)
The COVID-19 pandemic is one of the worst public health crises in a century, with an expected amount of deaths of several millions worldwide and an even bigger number of bereaved people left behind. Despite the consequences of this crisis are still unknown, a significant number of bereaved people will arguably develop Complicated Grief (CG) in the aftermath this emergency. If the current pandemic is unprecedented, the grief following the coronavirus outbreak is likely to share features with griefs related to natural disasters and after Intensive Care Unit (ICU) treatment. The aim of this paper is to review the most prominent literature on CG after natural disasters, as well as after diseases requesting ICU treatment. Such body of evidence may be useful for handling bereaved people during the acute phase of the COVID-19 pandemic and for drawing clinical attention to people at risk for CG.